THE ROLE OF WOMEN IN THE NOVEL GARIS PEREMPUAN BY SANIE B. KUNCORO AND NOVEL TEMPURUNG BY OKA RUSMINI (A COMPARATIVE LITERATURE STUDY) - Suerna Suerna (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2016)
This research aims to examine in depth the role of women in two novel Garis Perempuan and Tempurung. The role of women in the field of social, cultural, educational, and economic conteks. Then to compare all those roles and summed and find the relevance in education.This study used a qualitative descriptive method with a structural approach and the approach of comparative literature that discusses. 1) a description of each character, setting, and plot lines in the both novels. (2) the roles of women in the field of socio-cultural, educational, and economic,3) comparison of the role of women in the those two novels, (4) the relevance of the role of women in education. The research data in the form of a statement contains of sentences or paragraphs include narrative, dialogue or monologue, as well as interviews with researcher colleagues.Novel Garis Perempuan and Tempurung tells about the struggle of women in playing their roles in various fields such as the social field of culture, education, and economics.In order to play those roles they have to choose; worth of free choice or value. The role of women as mothers was found to be a figure or a model of all those women in struggle. Penilitian ini bertujuan untuk mengkaji secara mendalam peran perempuan dalam novel Garis Perempuan dan novel Tempurung. Peran perempuan dibidang sosial budaya, pendidikan, dan ekonomi, lalu membandingkan peran-peran tersebut kemudian menyimpulkan dan menarik relevansinya dengan pendidikan.Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan struktural dan pendekatan sastra bandingan yang membahas tentang (1) deskripsi masing-masing tokoh, latar, dan alaur novel Garis Perempuan dan novel Tempurung, (2) peran-peran perempuan dibidang sosial budaya, pendidikan, dan ekonomi, (3) perbandingan peran perempuan di dua novel, (4) relevansi peran perempuan dengan pendidikan. Data penelitian berupa pernyataan yang berupa kalimat atau paragraf yang berupa narasi, dialog, ataupun monolog, serta wawancara peneliti dengan rekan sejawat.Novel Garis Perempuan dan novel Tempurung mengisahkan tentang perjuangan perempuan dalam memerankan perannya diberbagai bidang seperti dibidang sosial budaya, pendidikan, dan ekonomi. Dalam rangka memerankan peran ini mereka harus memilih; pilihan senilai atau bebas nilai. Peran perempuan sebagai ibu ternyata dapat menjadi figur atau contoh dalam sebuah perjuangan.